2016
DOI: 10.7567/jjap.55.115504
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of a high-mobility FET with a cloud-aligned composite oxide semiconductor

Abstract: We have recently discovered that films of a widely used In–Ga–Zn oxide (IGZO) with have different material composition states when sputter-deposited under different conditions using the same polycrystalline IGZO target. Significant improvements in on-state current and mobility (as high as 40 cm2·V−1·s−1) are obtained. The results of local composition analysis indicate that the deposited film is not composed of any known homogeneous IGZO compound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…We have confirmed the existence of an amorphous structure only in simulation . CAAC‐IGZO is a crystalline phase that has a structure in the boundary region between an amorphous structure and a crystal structure, including single crystal and polycrystal …”
Section: Caac‐igzomentioning
confidence: 62%
See 1 more Smart Citation
“…We have confirmed the existence of an amorphous structure only in simulation . CAAC‐IGZO is a crystalline phase that has a structure in the boundary region between an amorphous structure and a crystal structure, including single crystal and polycrystal …”
Section: Caac‐igzomentioning
confidence: 62%
“…18,19 CAAC-IGZO is a crystalline phase that has a structure in the boundary region between an amorphous structure and a crystal structure, including single crystal and polycrystal. [20][21][22][23][24][25] Dr. Noboru Kimizuka, who first synthesized single-crystalline IGZO, 1,2,26 indicated that the crystal morphology of CAAC 21 and nanocrystal (nc) [22][23][24] should be classified as an intermediate state that is neither an amorphous structure nor a crystal structure. Similarly, Dr. Yoshio Waseda mentioned that CAAC and nc should be put in the category of a novel boundary region.…”
Section: Caac-igzomentioning
confidence: 99%
“…Additionally, CAAC-OS FETs have the advantage of exhibiting an extremely low off-state current, making them suitable for display applications. Figure 2A indicates that even when the channel length of the [11][12][13][14][15][16][17][18][19][20] CAAC-OS FET employed as a driving FET is scaleddown to 200 nm, the off-state current remained lower than 1 × 10 −12 A, which is below the measurement limit. Therefore, when the display shows black, the amount of electric current that flows would be extremely small, leading to a low-power consumption.…”
Section: Properties Of Caac-os Fetmentioning
confidence: 99%
“…The OS-FETs in both the layers have normally-off characteristics and their off-state currents are below the measurement limit. Novel boundary region [14] Amorphous [12,13] Crystalline Crystal [2,3,11] completely ・ CAAC [6] (2009) ・ single crystal amorphous ・ nc [7][8][9] (2013) ・ poly crystal ・ CAC [10] (2016) excluding single crystal and poly crystal "Intermediate state" [ 3…”
Section: Characteristics Of Stacked Os-fetsmentioning
confidence: 99%
“…Figure 1 shows classification of IGZO crystal structures. We have discovered c-axis aligned crystalline IGZO (CAAC-IGZO) [6], nanocrystalline IGZO (nc-IGZO) [7][8][9], and cloud-aligned composite IGZO (CAC-IGZO) [10], which, according to Kimizuka, have a structure with an "intermediate state" between an amorphous structure and a crystal structure [15]. We thus classify CAAC-IGZO, nc-IGZO, and CAC-IGZO as crystalline IGZO.…”
Section: Introductionmentioning
confidence: 99%